Insights into the procurement and distribution of fossiliferous chert artefacts across southern Australia from the archival record. Issue 2 (4th May 2019) - Ward, Ingrid; Key, Marcus M.; Riera, Rosine; Carson, Annie; O'Leary, Michael
Abstract: Following from previous research in Western Australia, this study explores the use of embedded microfossils—including bryozoan and foraminiferal fossil assemblages—to help identify source and distribution of fossiliferous chert artefacts from South Australian archives. Artefacts from key archaeological sites include Allen's Cave, Koonalda Cave, Wilson's Bluff, Ooldea and Kongarong. Preliminary analyses indicate a possible differentiation of fossiliferous chert types east and west of the Eyre Peninsula, from Otway Basin and Eucla Basin limestones, respectively. The widespread distribution and trade of fossiliferous chert is supported by ethnographic descriptions of the sources, procurement and trade as recorded by Daisy Bates, Thomas Draper Campbell and Norman Tindale. Further work combining biostratigraphy and lithology with archaeology and ethnography is needed to explore these ideas further.